Adapting of marketing research methodology “Mystery Shopping” to the specifics of retail self-service shops - Yu.K. Antipona; D.V. Sorochan (Marketing i Menedžment Innovacij, 2012)
The article shows the innovational approaches of carrying out marketing research of the service quality in the retail self-service shops with the help of Mystery Shopping method. The algorithm of making marketing research Mystery Shopping in the self-service shops was developed.